Performance of mathematics teachers to build students' high order thinking skills (HOTS) - Hardi Tambunan; Tutiarny Naibaho (Journal of Education and Learning (EduLearn), 2019)
The purpose of this study is to determine the mathematics teacher performance category in building high order thinking skills (HOTS) of students. The study was conducted on 560 students taken randomly from ten junior high schools and eight high schools from eight districts in North Sumatra Province. Data collection techniques and instruments are carried out by giving questionnaires to students which contain a number of questions about students' assessment of the mathematics teacher's performance in constructing the HOTS indicator. Based on descriptive analysis, it was found that the performance of mathematics teachers built HOTS indicators, namely (1) understanding of concepts, (2) mathematical communication, (3) creativity, (4) problem solving, and (5) reasoning is enough category. The results of analysis of variance show that teacher performance builds (1) understanding of concepts, (2) mathematical communication, (3) creativity, (4) problem solving, and (5) reasoning significantly influences students' abilities.